3D-microenvironments initiate TCF4 expression rescuing nuclear β-catenin activity in MCF-7 breast cancer cells. (February 2020) - Sergio, Sara; Coluccia, Addolorata Maria Luce; Lemma, Enrico Domenico; Spagnolo, Barbara; Vergara, Daniele; Maffia, Michele; De Vittorio, Massimo; Pisanello, Ferruccio
Abstract: Mechanical cues sensed by tumor cells in their microenvironment can influence important mechanisms including adhesion, invasion and proliferation. However, a common mechanosensitive protein and/or pathway can be regulated in different ways among diverse types of tumors. Of particular interest are human breast epithelial cancers, which markedly exhibit a heterogeneous pattern of nuclear β-catenin localization, a protein known to be involved in both mechanotransduction and tumorigenesis. β-catenin can be aberrantly accumulated in the nucleus wherein it binds to and activates lymphoid enhancer factor/T cell factor (LEF/TCF) transcription factors. At present, little is known about how mechanical cues are integrated into breast cancer cells harboring impaired mechanisms of β-catenin's nuclear uptake and/or retention. This prompted us to investigate the influence of mechanical cues on MCF-7 human breast cancer cells which are known to fail in relocating β-catenin into the nucleus due to very low baseline levels of LEF/TCFs. Exploiting three-dimensional (3D) microscaffolds realized by two-photon lithography, we show that surrounding MCF-7 cells have not only a nuclear pool of β-catenin, but also rescue from their defective expression of TCF4 and boost invasiveness. Together with heightened amounts of vimentin, a β-catenin/TCF-target gene regulator of proliferation and invasiveness, such 3D-elicited changes indicate an epithelial-to-mesenchymal phenotypic switch of MCF-7 cells. This is also consistent with an increased in situ MCF-7 cell proliferation that can be abrogated by blocking β-catenin/TCF-transcription activity. Collectively, these data suggest that 3D microenvironments are per se sufficient to prime a TCF4-dependent rescuing of β-catenin nuclear activity in MCF-7 cells. The employed methodology could, therefore, provide a mechanism-based rationale to dissect further aspects of mechanotranscription in breast cancerogenesis, somewhat independent of β-catenin's nuclear accumulation. More importantly, by considering the heterogeneity of β-catenin signaling pathway in breast cancer patients, these data may open alternative avenues for personalized disease management and prevention. Statement of significance: Mechanical cues play a critical role in cancer pathogenesis. Little is known about their influence in breast cancer cells harboring impaired mechanisms of β-catenin's nuclear uptake and/or retention, involved in both mechanotransduction and tumorigenesis. We engineered 3D scaffold, by two-photon lithography, to study the influence of mechanical cues on MCF-7 cells which are known to fail in relocating β-catenin into the nucleus. We found that 3D microenvironments are per se sufficient to prime a TCF4-dependent rescuing of β-catenin nuclear activity that boost cell proliferation and invasiveness. Thus, let us suggest that our system could provide a mechanism-based rationale to further dissect key aspects of mechanotranscription in breast cancerogenesis and progression, somewhat independent of β-catenin's nuclear accumulation. Graphical abstract: Image, graphical abstract